Analyse variationnelle et numérique de quelques problèmes viscoélastiques - Debbacha , Laifa; LEBRI , NEMIRA Supervisor; MEROUANI , Adbelbaki Co- Supervisor (Université Sétif 1 - Ferhat ABBAS , Faculté des Sciences, 2026)
The purpose of this work is to study some problems in contact mechanics involving piezoelectric, elasto-viscoplastic, and thermo-electro-viscoelastic constitutive laws with long- term memory. The obtained results concern the existence and uniqueness of a weak solution to the studied problems. The thesis is structured in two parts: The first part recalls various contact mechanical models and presents the necessary Mathematical tools. The second part focuses on the modeling and mathematical analysis of the considered contact problems. A numerical approach is also carried out for two problems using a finite element scheme with implicit time discretization
هدف هذه الاطروحة هو دراسة بعض المسا ئل في ميكانيك التماس المرتبطة بقوانين تأسيسية كهرضغطية مرنة-لزوجية- لدنة و حرارية-كهربائية- لزوجية ذات ذاكرة طويلة. النتائج المتحصل عليها تتعلق بوجود و تفرد الحل الضعيف للمشكلات المدروسة. تنقسم الاطروحة الئ جزئين الجزء الأول مخصص لتقديم النماذج الميكانيكية المختلفة للتلامس ’ بالاضافة الئ بعض الادوات الرياضية الضرورية. أما الجزء الثاني فيركز علئ النمذجة و الدراسة الرياضية للمشكلات المطروحة مع تناول المقاربة العددية لمشكلتين باستخدام طريقة العناصر المنتهية و تقطيع زمني ضمني
Keywords: : Endommagement; Compliance normale; Contact unilatéral; Élastique; Électro- Elastique; Électro-élasto-viscoplastique; Éléments finis; Point fixe; Inéquation d’évolution